Vaccinal prevention of infectious diseases in adults - N. I. Briko; I. V. Feldblium; K. A. Subbotina; A. V. Bikmieva; N. N. Tsapkova; E. A. Boiko (Журнал инфектологии)
The results of foreign and Russian author`s researches about  immunization of adult population are presented in article. The analysis  of the vaccinal prevention state of infectious diseases in adults in  different countries of the world (national guidance on adults  immunization, coverage of preventive vaccinations, financing  mechanisms) is given. The tasks of improving immunization in adult  population of Russia are defined.